Hepatitis E virus: Efficacy of pasteurization of plasma‐derived VWF/FVIII concentrate determined by pig bioassay. Issue 4 (19th February 2021) - Dähnert, Lisa; Schlosser, Josephine; Fast, Christine; Fröhlich, Andreas; Gröner, Albrecht; Lange, Elke; Roth, Nathan J.; Schäfer, Wolfram; Schröder, Charlotte; Eiden, Martin; Groschup, Martin H.
Abstract: Background: Hepatitis E virus (HEV) is the leading cause of acute hepatitis throughout the world. Increasing blood component transfusion‐associated HEV infections highlight the need for reliable virus inactivation procedures for plasma derivatives from pooled plasma donations. Study Design and Methods: An animal infection study was conducted to evaluate the efficiency of HEV inactivation by pasteurization during the manufacturing process of the von Willebrand Factor/Factor VIII (VWF/FVIII) concentrate Haemate P/Humate‐P (CSL Behring, Marburg, Germany). For this purpose, groups of pigs were inoculated with stabilized VWF/FVIII intermediate spiked with HEV‐positive liver homogenate and exposed to increasing incubation times of 0, 3, 6, and 10 h at 60°C. Animals were evaluated for virus replication over 27 days and in a subsequent trial over 92 days. Results: Virus replication was detected in animals up to the 6‐h pasteurization group. In contrast, pasteurization for 10 h did not reveal virus detection when the observation period was 27 days. In an additional experiment using the 10‐h pasteurized material, two individuals started virus excretion and seroconverted when the observation period was extended to 92 days. Based on the total infection rate (2 of 12) of the animals inoculated with the sample pasteurized for 10 h, a virus reduction factor of at least 4.7 log10 is calculated. Conclusion: This study demonstrates that pasteurization at 60°C for 10 h of an HEV‐positive plasma derivative leads to the effective reduction of infectivity, resulting in a VWF/FVIII product with an appropriate margin of safety for HEV.